2010
DOI: 10.5650/jos.59.15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fatty Hydroxamic Acids from Triacylglycerides

Abstract: In this study, fatty haydroxamic acids (FHAs), which have biological activities as antibiotics and antifungal, have been synthesized via refluxing of triacylglycrides, palm olein, palm stearin or corn oil with hydroxylamine hydrochloride. The products were characterized using the complex formation test of hydroxamic acid group with zinc( ), copper( ) and iron( ), various technique methods including nuclear magnetic resonance ( 1 H NMR) spectroscopy, Fourier transform infrared (FTIR) spectroscopy and elemental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The first commercial clay nano-composite was prepared via an ion exchanging process (Ray and Okamoto, 2003;Giannelis, 1996). Recently, many studies were reported for MMT modification using alkylammonium ions produced from vegetable oils (Al-Mulla et al, 2009;Al-Mulla et al, 2010a;Hoidy et al, 2010a;Hoidy et al, 2010b).…”
Section: Modification Of Claymentioning
confidence: 99%
“…The first commercial clay nano-composite was prepared via an ion exchanging process (Ray and Okamoto, 2003;Giannelis, 1996). Recently, many studies were reported for MMT modification using alkylammonium ions produced from vegetable oils (Al-Mulla et al, 2009;Al-Mulla et al, 2010a;Hoidy et al, 2010a;Hoidy et al, 2010b).…”
Section: Modification Of Claymentioning
confidence: 99%
“…Cation exchange and intercalation processes were characterized by the existence of cations encountered in the interlayer of bentonite such as (Na + , Mg ) in the some clay minerals such as bentonite and intercalant cations such as Ti, Zr, AI and Cr [3]. The intercalation processes was easily done by mixing the dispersion of bentonite in water containing intercalant cations and by adding the polar organic such as glycerol or ethylene glycol [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lipase (triacylglycerol hydrolases; EC 3.1.1.3) is extensively used due to their regio-, stereo-, substrate-specificities milder reaction conditions and relatively lower energy requirement 2,4 . Lipase-catalyzed reactions have been carried out in suitable organic solvents or under solvent-free conditions at hydrolysis reaction 6 , esterification 7,8,9 and amidification 3,5,10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is fully biodegradable surfactant and cause less damage to the environment than petroleum chemical surfactants 2 . Fatty amide is the essential ingredient of several formulations such as detergent, shampoos, cosmetics, antibiotics and antifungal agents 3,4 .…”
Section: Introductionmentioning
confidence: 99%